PHP and Smarty on large scale web development - Pedro, Bruno (O'Reilly short cut., 2007)
With web development now being considered a commodity, projects are getting larger every day. If you are dealing with large projects on a daily basis, you know that the most difficult task is to deliver products on time and within a budget. However, many factors can influence those variables, including the programming language development methods you choose. This Short Cut shows you what a good choice it is to use PHP and Smarty for large-scale web projects. If you follow the principles and methodologies described here, you'll achieve greater productivity in your development tasks.